# HOW TO SOLVE 5(3-x)+1=3(x+4)?

hello friends,
Welcome to my article 5(3-x)+1=3(x+4)
This article has been taken from the simplification lesson, in this article we have been told to simplify with the action of addition, subtraction, multiplication, division and fractions.
For complete information on how to solve this 5(3-x)+1=3(x+4), read and understand it carefully.

First of all we should write the article on the page of the notebook.

## 5(3-x)+1=3(x+4)

Let’s solve it by placing ,

\displaystyle 5(3-x)+1=3(x+4)

We are seeing that in this question small cost has been used, so first of all we will solve it by breaking small cost.

\displaystyle 15-15x+1=3x+12

\displaystyle -15x-3x=12-16

\displaystyle -18x=-4

\displaystyle x=-\frac{4}{{18}}

This article has been completely solved by tireless effort from our side, still if any error remains in it then definitely write us your opinion in the comment box. If you like or understand the methods of solving all the questions in this article, then send it to your friends who are in need.

Note: If you have any such question, then definitely send it by writing in our comment box to get the answer.

## See more such example no.-01

How to solve ,2(3x-4)+2(2-4x)=7(3-2x)?

2(3x-4)+2(2-4x)=7(3-2x)

First of all we should write the article on the page of the notebook.

\displaystyle 2(3x-4)+2(2-4x)=7(3-2x)

We are seeing that in this question small cost has been used, so first of all we will solve it by breaking small cost.

\displaystyle 2\text{x}3x-2\text{x}4+2\text{x}2-2\text{x}4x=7\text{x}3-7\text{x}2x

Solving homogeneous algebraic terms together by putting homogeneous algebraic terms together.

\displaystyle 6x-8x-8+4=21-14x

\displaystyle -2x-4=21-14x

on transposition,

\displaystyle -2x+14x=21+4

\displaystyle 12x=25

\displaystyle x=\frac{{25}}{{12}}

This article has been completely solved by tireless effort from our side, still if any error remains in it then definitely write us your opinion in the comment box. If you like or understand the methods of solving all the questions in this article, then send it to your friends who are in need.

Note: If you have any such question, then definitely send it by writing in our comment box to get the answer.

## 2+7(x-2)+4(x+3)=7(x-3)?

First of all we should write the article on the page of the notebook.

2+7(x-2)+4(x+3)=7(x-3)

We are seeing that in this question small cost has been used, so first of all we will solve it by breaking small cost.

\displaystyle 2+7(x-2)+4(x+3)=7(x-3)

\displaystyle 2+7\text{x}x-7\text{x}2+4\text{x}x+4\text{x}3=7\text{x}x-7\text{x}3

\displaystyle 2+7x-14+4x+12=7x-21

Solving homogeneous algebraic terms together by putting homogeneous algebraic terms together.

\displaystyle 7x+4x-14+12+2=7x-21

\displaystyle 11x-14+14=7x-21

Now we know that the solution for -14 and +14 is 0.

hence,

\displaystyle 11x=7x-21

on transposition,

\displaystyle 11x-7x=-21

\displaystyle 4x=-21

\displaystyle x=-\frac{{21}}{4}

Therefore,